Letter (copy) : Spain - Citrine, Walter, 1887-1983
011-0061-001 Situation WMC/WJB/AC/939 Esp.263 International 9th August, 1937 Mr. Schevenels International Federation of Trade Unions, 9, avenue d'Orsay, PARIS VIIe. Dear Comrade Schevenels, Spain In reply to your circular letter of 9th ultimo with regard to continuing propagande for our Spanish comrades, we circularised all branches of our Trade Union and Labour Movement, informing them that it had been decided that propaganda meetings should be held during the first week in August. It was recognised, however, that, in our country, it was not very easy during this period to secure satisfactory meetings, because of the occurrence of the Bank Holiday. It was therefore recommended to our affiliated organisations that they should use such opportunities throughout the month as they might feel were most useful for the purpose. The decisions of the meetings are being conveyed by telegram and letter to the Secretary of State for Foreign Affairs. For your information, we enclose a copy of the circular with the special manifesto that accompanied it. This was published in the press, and distributed to all branches of our Movement. Yours faithfully, General Secretary Circular; manifesto. 292/946/11/61